2016
DOI: 10.1136/tobaccocontrol-2016-053265
|View full text |Cite
|
Sign up to set email alerts
|

Misperceptions of harm among Natural American Spirit smokers: results from wave 1 of the Population Assessment of Tobacco and Health (PATH) study (2013–2014)

Abstract: The majority of NAS smokers inaccurately believes that their cigarettes are less harmful than other brands. Given the brand's rapid growth and its more common use in vulnerable groups (eg, young adults, lesbian, gay, bisexual, 'other' or 'questioning' adults), corrective messaging and enforcement action are necessary to correct harm misperceptions of NAS cigarettes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 39 publications
6
36
0
Order By: Relevance
“…Indeed, participants reported that approximately half of their closest friends smoked. Preferred cigarette brands were consistent with brand preference in the general population (Marlboro, Camel (Schleicher, Johnson, Rigdon, et al, 2017)) and the SGM population (Natural American Spirit (Pearson, Johnson, Villanti, et al, 2017)). Notably, participants' average subjective social status compared to others in the U.S. and in their communities was below the midpoint of the scale.…”
Section: Discussionsupporting
confidence: 53%
“…Indeed, participants reported that approximately half of their closest friends smoked. Preferred cigarette brands were consistent with brand preference in the general population (Marlboro, Camel (Schleicher, Johnson, Rigdon, et al, 2017)) and the SGM population (Natural American Spirit (Pearson, Johnson, Villanti, et al, 2017)). Notably, participants' average subjective social status compared to others in the U.S. and in their communities was below the midpoint of the scale.…”
Section: Discussionsupporting
confidence: 53%
“…A majority of American Spirit smokers reported this belief, despite the brand’s disclaimers. Pearson et al 14 likewise found using PATH data that nearly 64% of American Spirit smokers inaccurately believed that their brand was less harmful than other cigarette brands. But it is not only textual descriptors like ‘natural’ that matter in shaping user perceptions, as Moran et al 15 show in an analysis of American Spirit advertising.…”
mentioning
confidence: 99%
“…The belief that natural ingredients are safer can be linked to a more general belief that natural alternatives are superior to artificial ones. For example, people expect organic tobacco to be safer [45], natural perfumes to smell better [46], or organic food to have fewer calories [47]. Similarly, there is a general belief that human tampering with nature is risky [48].…”
Section: General Beliefs About the Safety Of What Is Naturalmentioning
confidence: 99%